The Russia-Ukraine conflict: its implications for the global food supply chains - Jagtap, Sandeep; Trollman, Hana; Trollman, Frank; Garcia-Garcia, Guillermo; Parra-López, Carlos; Duong, Linh; Martindale, Wayne; Munekata, Paulo E. S.; Lorenzo, Jose M.; Hdaifeh, Ammar; Hassoun, Abdo; Salonitis, Konstantinos; et al. (MDPI, 2022)
Food is one of the most traded goods, and the conflict in Ukraine, one of the European breadbaskets, has triggered a significant additional disruption in the global food supply chains after the COVID-19 impact. The disruption to food output, supply chains, availability, and affordability could have a long-standing impact. As a result, the availability and supply of a wide range of food raw materials and finished food products are under threat, and global markets have seen recent increases in food prices. Furthermore, the Russian-Ukrainian conflict has adversely affected food supply chains, with significant effects on production, sourcing, manufacturing, processing, logistics, and significant shifts in demand between nations reliant on imports from Ukraine. This paper aims to analyze the impacts of the conflict between Russia and Ukraine on the effectiveness and responsiveness of the global food supply chains. A PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, including grey literature, was deployed to investigate six key areas of the food supply chains that would be impacted most due to the ongoing war. Findings include solutions and strategies to mitigate supply chain impacts such as alternative food raw materials, suppliers and supply chain partners supported by technological innovations to ensure food safety and quality in warlike situations.
Keywords: conflict; consumer; food processing; food production; food logistics; food quality; food storage; food supply chain; Russia; Ukraine; war